The development of ultrasonographic diagnosis criteria for cholecystitis differentiation in dogs - Shkvarya, Mikola; Shkvaria, M. M.; Shkvaria, N. N.; Shkvarya, M. M.; Shkvarya, N. N.; Shkvaria, Mikola; Shkvaria, Nikolai; Shkvarya, Nikolai; Shkvarya, M.; Шкваря, Микола Миколайович; Semonov, Oleksandr; Semyonov, O. V.; et al. (Дніпровський ДАЕУ, 2024)
The paper presents the results of research of diagnosis and stage determination peculiarities of cholecystitis in dogs. In general, the clinical, differential diagnostic and ultrasonographic stages of the course of cholecystitis were studied. An important clinical and diagnostic tool for the diagnosis of cholecystitis in dogs is the application of the ultrasonographic examination. The study included 64 dogs, which were examined to diagnose cholecystitis. Three groups of dogs were identified: 17 dogs (27% of cases) were affected with initial stage of cholecystitis, 26 dogs (40% of cases) were affected with intermediate and 21 dogs (33%) were affected with late stage. The main clinical symptoms of the first stage of the gallbladder inflammation consisted of anorexia, vomiting, abdominal wall pain. The ultrasonographic picture was characterized by the presence of a hyperechoic wall of the gallbladder, an increase in the thickness of its wall, and a thickening of the mucous layer. Following mentioned symptoms including anorexia, weight loss, the presence of vomiting, decreased skin turgor, icterus of the mucous membranes, and abdominal wall pain were chosen as the main clinical symptoms of the 2nd stage of the gallbladder inflammation. Morphological signs that were selected for the diagnosis of cholecystitis were investigated by ultrasonography, including the presence of the wall hyperechoicity, thickening of the gallbladder wall, thickening of the mucous membrane layer, the presence of a suspension (mucocele) in the gallbladder and hyperechoic calculi. Presence of anorexia, a decrease in body weight, the presence of vomiting, a decrease in skin turgor, icterus of the mucous membranes, tenderness of the abdominal wall during palpation were chosen as the main clinical symptoms of the 3rd stage of gallbladder inflammation. During the 3rd stage of cholecystitis in dogs, the following signs were determined by ultrasonography: hyperechogenicity and heteroechogenicity of the gallbladder wall, thickening of the mucous membrane of the gallbladder; the presence of erosions on the mucous membrane, the presence of mucocele and hyperechoic calculi up to 5-7 mm in the gallbladder. У статті наведено результати дослідження особливостей діагностики та визначення стадії холециститу у собак. В цілому вивчено клінічну, диференціально-діагностичну та ультразвукову стадії перебігу холециститу. Важливим клініко-діагностичним засобом діагностики холециститу у собак є застосування ультразвукового дослідження. У дослідженні взяли участь 64 собаки, яких обстежили з метою діагностики холециститу. Було виділено три групи собак: 17 собак (27% випадків) були уражені початковою стадією холециститу, 26 собак (40% випадків) були уражені середньою та 21 собака (33%) були уражені пізньою стадією. Основними клінічними симптомами І стадії запалення жовчного міхура були анорексія, блювання, біль у черевній стінці. Ультразвукова картина характеризувалася наявністю гіперехогенної стінки жовчного міхура, збільшенням товщини його стінки, потовщенням слизового шару. Основними клінічними симптомами 2-ї стадії запалення жовчного міхура були обрані наступні симптоми: анорексія, втрата маси тіла, наявність блювання, зниження тургору шкіри, жовтяниця слизових оболонок, біль у черевній стінці. За допомогою УЗД досліджували морфологічні ознаки, відібрані для діагностики холециститу, у тому числі наявність гіперехогенності стінки, потовщення стінки жовчного міхура, потовщення шару слизової оболонки, наявність суспензії (мукоцеле) в жовчному міхурі та гіперехогенних конкрементів. . Основними клінічними симптомами 3 стадії запалення жовчного міхура обрано наявність анорексії, зниження маси тіла, наявність блювоти, зниження тургору шкіри, жовтяницю слизових оболонок, болючість черевної стінки при пальпації. При 3-й стадії холециститу у собак за допомогою УЗД виявлено: гіперехогенність та гетероехогенність стінки жовчного міхура, потовщення слизової оболонки жовчного міхура; наявність ерозій на слизовій оболонці, наявність мукоцеле і гіперехогенних конкрементів до 5-7 мм в жовчному міхурі.
Розробка критеріїв ультрасонографічної діагностики холециститу у собак
Шкваря Микола Миколайович https://orcid.org/0000-0001-7279-3642 Семьонов Олександр Володимирович https://orcid.org/0000-0002-8562-4108 Cуслова Наталія Іванівна https://orcid.org/0000-0001-9500-9224
Keywords: gall bladder; жовчний міхур; dogs; собаки; cholecystitis; холецистит